Gynecological Cancer in Middle Euphrates Region of Iraq , 2012-2020 - Mjali, Ahmed; Jawad, Safaa Ayad; Al Baroodi, Bushra Najeh Hasan (Asian Pacific Journal of Environment and Cancer, 2020)
short communication